Using Standardized Lexicons for Report Template Validation with LexMap, a Web-based Application. - Hostetter, Jason; Wang, Kenneth; Siegel, Eliot; Durack, Jeremy; Morrison, James (Journal of Digital Imaging, 2015)
An enormous amount of data exists in unstructured diagnostic and interventional radiology reports. Free text or non-standardized terminologies limit the ability to parse, extract, and analyze these report data elements. Medical lexicons and ontologies contain standardized terms for relevant concepts including disease entities, radiographic technique, and findings. The use of standardized terms offers the potential to improve reporting consistency and facilitate computer analysis. The purpose of this project was to implement an interface to aid in the creation of standards-compliant reporting templates for use in interventional radiology. Non-standardized procedure report text was analyzed and referenced to RadLex, SNOMED-CT, and LOINC. Using JavaScript, a web application was developed which determined whether exact terms or synonyms in reports existed within these three reference resources. The NCBO BioPortal Annotator web service was used to map terms, and output from this application was used to create an interactive annotated version of the original report. The application was successfully used to analyze and modify five distinct reports for the Society of Interventional Radiology's standardized reporting project.